1998
DOI: 10.2466/pms.1998.86.3.883
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Method and Motor Activity in 3-Month-Old Human Infants

Abstract: It is currently acknowledged that breast-fed and formula-fed infants exhibit different rates of physical growth. Little is known, however, about behavioral differences that may be attributable to early feeding method. In the present investigation, activity level in 3-mo.-old infants was examined by measuring motoric output in 40 breast-fed and 40 formula-fed infants. Maternal ratings of temperament did not differ across the two groups, but scores derived from the actometer in a laboratory setting showed breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
0
10
1
1
Order By: Relevance
“…With this in mind, it is not surprising that more challenging temperaments were seen in breastfed infants at age three months in our study. However, previous studies among three-month-old infants found no associations between breastfeeding and infant temperament [12], [14], [16]. This discrepancy could be due to the larger sample size of our study; those earlier studies each involved less than 60 infants.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…With this in mind, it is not surprising that more challenging temperaments were seen in breastfed infants at age three months in our study. However, previous studies among three-month-old infants found no associations between breastfeeding and infant temperament [12], [14], [16]. This discrepancy could be due to the larger sample size of our study; those earlier studies each involved less than 60 infants.…”
Section: Discussioncontrasting
confidence: 73%
“…It is possible that continuing difficult temperament in some breastfed infants may contribute to the steady decline in breastfeeding prevalence with increasing infant age. However, previous small studies failed to show any relationship between breastfeeding and infant temperament assessed at age three months by infant behaviour questionnaires or direct observation of mother-infant interaction [12], [14], [15], [16]. Furthermore, in an observational comparison between the control groups of a randomised controlled trial, temperament did not differ between older breastfed or formula-fed infants at age six to twelve months old [17].…”
Section: Introductionmentioning
confidence: 79%
“…Mothers' milk differs substantially from formula in many respects, including essential fatty acid constituents. In particular, the essential fatty acid docosahexanoic acid (DHA), which is present in breast milk but absent in formula, has been implicated in a variety of neurodevelopmental variables, including cognitive and educational achievement [Horwood & Fergusson, 1998], visual acuity and attention [Reisbick et al, 1997], and (potentially) motor activity [Worobey, 1998], to name a few. However, nursery-reared rhesus infants fed a DHA-supplemented formula show similar cortisol and ACTH values to infants fed a standard formula [Champoux, unpub.…”
Section: Discussionmentioning
confidence: 99%
“…Também examinamos, no modelo, se padrões de transição de comportamento alimentar poderiam estar associados com o desfecho, utilizando a idade do abandono da mamadeira como indicador desse processo. Embora não tenha havido associação no modelo ajustado, alguns estudos têm sugerido que a transição tardia para alimentação sólida e o desmame precoce poderiam contribuir para um padrão menos ativo entre os lactentes, mostrando, no entanto, resultados discrepantes e inconclusivos 18,19 .…”
Section: Discussionunclassified